Active MMW/Terahertz Security System Based on Bessel Beams. (27th May 2013) - Minin, Igor; Minin, Oleg
Abstract : The novel concept of the security system based on THz Bessel beams is offered. The system is based on a novel THz diffractive optics for scanning the person (without the application of THz laser) and on a sensitive scheme for the detection of the reflected and scattered THz radiation. The development of enabling technology, namely, sensitive detector arrays and Millimeter wave/THz diffractive optics, will allow building compact, easy-to-use millimeter wave/THz imaging systems without expensive cost THz laser. The scanning properties of diffractive optics for Bessel beam are investigated.